Evaluation of the expression of induced genes in response to dehydration stress of Camelina (Camelina sativa) calli: Dehydration stress genes in Camelina - Ghorbani, Masoumeh; Kahrizi, Danial; Chaghakaboodi, Zeinab; Ercişli, Sezai (Cellular and Molecular Biology, 2022)
Plants are constantly exposed to various biological and non-biological stresses that endanger their lives. Drought stress is one of the abiotic stresses that have a great impact on the yield and life of plants and is one of the main causes of reduced crop yields. Reducing the effects of environmental stresses such as drought using methods such as irrigation, fertilizer application and appropriate planting methods is limited. Therefore, genetic modification of plants is an important effort to minimize the effect of environmental stresses. in this research, Twenty disinfected camelina seeds were cultured on the MS medium containing 3% sucrose, 0.8% agar and pH 5.8 under a laminar hood. After 14 days, the cotyledon explants (about 1 cm) were separated from the seedlings and placed on the callus induction medium. The MS callus induction medium containing 0.5 mg / l kinetin, 2 mg / l -2,4 D, 3% sucrose, 0.8% agar and pH 5.8. Samples were subcultured every two weeks to the same medium and calli were formed after 4 weeks. Then the calli were transferred to the medium containing a concentration of 30% PEG. To study gene expression, first callus samples were treated with liquid nitrogen and to study the effect of drought stress on gene expression, this sample was sent to Zagros Bioidea Company located in the Razi University Incubator. Gene expression was performed through microarray technology. The results showed that seven different genes whose expression increased by almost six times the control value can be mentioned, including Cold-acclimation protein (CAP160), NAC10, Abscisic acid (ABA), ABF4, CRK3, lysM domain receptor-like kinases (LYKs) and Basic/helix-loop-helix(bHLH130-like). Drought tolerance is not a genetically simple trait, but a quantitative and complex trait with various aspects that require the use of molecular methods to investigate the relevant mechanisms. This study aimed to investigate the expression of different genes of callus tissues of the Camelina plant under stress and non-stress conditions by microarray method.